1992
DOI: 10.1159/000186827
|View full text |Cite
|
Sign up to set email alerts
|

Renal Involvement in Sickle Cell-Beta Thalassemia

Abstract: Renal function studies were performed in 41 patients with sickle cell-β thalassaemia (S/b thai) and compared to 14 normal controls and 8 sickle cell (SS) patients. Polyuria, hyposthenuria and mild proteinuria were common in both S/b thai and SS patients. A renal concentrating defect was manifest in all patients studied, and in 4 of the 7 S/b thai patients tested, an abnormal acidification test was found. A statistically significant negative correlation (n=19, r = -0.48, p < 0.05) was noted between creatinine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Low levels of hemoglobin raised beta 2-microglobulin, NAG and Cystatin-C. This was the evidence of that chronic hypoxia due to anemia disrupted kidney function [15,16]. In our study, urea levels of thalassemia group were found significantly high in the control group (p<0.05).…”
Section: Discussionsupporting
confidence: 60%
“…Low levels of hemoglobin raised beta 2-microglobulin, NAG and Cystatin-C. This was the evidence of that chronic hypoxia due to anemia disrupted kidney function [15,16]. In our study, urea levels of thalassemia group were found significantly high in the control group (p<0.05).…”
Section: Discussionsupporting
confidence: 60%
“…This urinary concentrating defect becomes apparent at an early age in SS individuals. The renal concentrating defect in sickle ␤-thalassemia may be as prominent as in sickle cell anemia, although in this and in the other SCDs, as well as in sickle cell trait, the concentrating defect becomes manifest much later in life [8,9]. After an 8-10 hr overnight water deprivation, the urine osmolality in SS patients was 414 ± 10 mmol/kg (mean ± SE), considerably lower than the values in normal subjects (911 ± 39 mmol/kg) [10].…”
Section: Abnormalities Of Distal Nephron Functionmentioning
confidence: 99%
“…Thus, although they had similar water intakes after dehydration, the SCD patients lost more fluid as urine than the normal subjects. These suggest that the SCD patients tend to remain in a state of water deficit, and may explain the most common defect in patients with SCD which is impaired urine concentrating ability or hyposthenuria (Kontessis et al, 1992) which is suggested in this study by the lower urine concentration index in these patients.…”
Section: Discussionmentioning
confidence: 54%